2016
DOI: 10.1021/acs.macromol.6b01333
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–Inorganic Composites with Dynamic Covalent Mechanochromophore

Abstract: Polymer–inorganic composites with diaryl­bibenzo­furanone (DABBF) moieties, dynamic covalent mechanochromophores, were prepared, and their mechanochromic behavior was systematically investigated. The central C–C bonds in DABBF moieties can be cleaved by mechanical force to form the corresponding stable blue radicals, which can be quantitatively evaluated by electron paramagnetic resonance (EPR) spectroscopy. One controversial issue but attractive property in the DABBF system is the equilibrium between the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 57 publications
(77 reference statements)
0
81
0
Order By: Relevance
“…The ultimate advantage of radical‐type mechanochromic polymers is not only the qualitative visualization of the mechanical stress, but also its quantitative evaluation by electron paramagnetic resonance (EPR) spectroscopy, both in solution and the solid state. We have already reported two radical‐type mechanochromic polymers that bear diarylbibenzofuranone (DABBF) or tetraarylsuccinonitrile (TASN) moieties (Figure a and b) . Homolytic cleavage of the central carbon‐carbon bond in the DABBF and TASN units in response to mechanical stress affords arylbenzofuranone (blue) and diarylacetonitrile radicals (pink), respectively.…”
Section: Figurementioning
confidence: 77%
“…The ultimate advantage of radical‐type mechanochromic polymers is not only the qualitative visualization of the mechanical stress, but also its quantitative evaluation by electron paramagnetic resonance (EPR) spectroscopy, both in solution and the solid state. We have already reported two radical‐type mechanochromic polymers that bear diarylbibenzofuranone (DABBF) or tetraarylsuccinonitrile (TASN) moieties (Figure a and b) . Homolytic cleavage of the central carbon‐carbon bond in the DABBF and TASN units in response to mechanical stress affords arylbenzofuranone (blue) and diarylacetonitrile radicals (pink), respectively.…”
Section: Figurementioning
confidence: 77%
“…The advantage of the proposed method over existing triggering methods is the capability to achieve spatiotemporal control of mechanophore activation. In particular, while previous studies have demonstrated mechanochemical activation in bulk polymers using compression and tension (3,4,8,45), the HIFU-based triggering system demonstrated here is a remote energy source capable of localizing the region of activation and triggering polymer mechanochemistry noninvasively. These advances enable mechanoactivation of two different mechanophore systems.…”
Section: Resultsmentioning
confidence: 93%
“…Good mechanical activation of the mechanophore diarylbibenzofuranone at the interface between silica particles and a rubbery poly(butyl acrylate) matrix was recently reported . The composite rubbers changed from colorless to blue when stretched because stable blue radicals formed.…”
Section: Mechanochromic Fiber‐reinforced Compositesmentioning
confidence: 99%